Cost-Effectiveness analysis model for civil aircraft flight tests. Issue 1 (1st August 2022) - Sun, Mingming; Duan, Xinyu; Liu, Qingling; Sun, Changtai; Song, Hao
Abstract: Flight tests for civil transport aircraft are a necessary condition for acquiring airworthiness type certification (TC) for new types of aircraft to enter the market. For commercial aircraft, cost control is an important consideration for aircraft development because flight tests are highly complex, time consuming and expensive. As a large and complex system, it is important to evaluate the cost-effectiveness of civil aircraft flight tests. However, due to the large number of and complex relationship between the factors involved in the project, it is extremely difficult to conduct a reasonable cost-effectiveness evaluation. Based upon the characteristics of the flight test mission, this paper analyzes the key indicators which have an important influence on the flight test project during the test, and proposes an operable and reasonable cost-effectiveness evaluation model, which provides the basis for the scientific decision-making of flight test planning.